2012
DOI: 10.1002/etc.1921
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and polyamine metabolism alterations in Rhinella arenarum embryos exposed to the organophosphate chlorpyrifos

Abstract: Organophosphorus pesticides (OPs) are widely applied in the Alto Valle of Río Negro and Neuquén, Argentina, due to intensive fruit growing. Amphibians are particularly sensitive to environmental pollution, and OPs may transiently accumulate in ponds and channels of the region during their reproductive season. Organophosphorus pesticide exposure may alter amphibian embryonic development and the reproductive success of autochthonous species. In the present study, embryos of the common toad Rhinella arenarum were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
(61 reference statements)
0
17
0
5
Order By: Relevance
“…The LC50 values for each stage were compared by Student s t test. The no observed effect concentration (NOEC) and lowest observed effect concentration (LOEC) values were statistically assessed from experimental data by ANOVA-Dunnet's test [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LC50 values for each stage were compared by Student s t test. The no observed effect concentration (NOEC) and lowest observed effect concentration (LOEC) values were statistically assessed from experimental data by ANOVA-Dunnet's test [14].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, water quality greatly influences the growth and development of this species [12]. It has been shown that R. arenarum has sensitivity toward diverse contaminants similar to other anurans [12][13][14]. Field studies have shown bioaccumulation of As both in tadpoles and adult amphibians at contaminated sites, as well as in laboratory-exposed tadpoles [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…When considering available data for chlorpyrifos, effects on anurans from different parts of the world have been evaluated at different levels, including the individual level (responses in terms of survival, development, growth, and morphology; Abbasi and Soni 1991;Cowman and Mazanti 2000;Kerby 2006;Bernabò et al 2011), the biochemical level (Richards and Kendall 2002;El-Merhibi et al 2004), and the genotoxic level (Yin et al 2009). Only few studies have evaluated the effects of chlorpyrifos on native anuran species from Argentina, at both the individual (Ruiz de Arcaute et al 2012;Salgado Costa et al 2018) and the biochemical (Sotomayor et al 2012(Sotomayor et al , 2015Attademo et al 2015;Liendro et al 2015) levels. Those sublethal effects on local species have been mostly reported at environmentally relevant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, their lower specificity and sensitivity compared with other biochemical targets such as enzymatic activities, other proteins, or metabolites serving as molecular targets or detoxifying pathways have led to a more generalized use. Therefore, the use of a battery of biomarkers covering different targets or pathways and different levels of biological organization has gained consensus (Venturino et al 2003; Ferrari et al 2011; Sotomayor et al 2012, 2015; Liendro et al 2015; Pérez‐Iglesias et al 2015; Natale et al 2018). However, in most studies the classical biomarker response is not tightly and consistently linked to responses at higher levels.…”
Section: Introductionmentioning
confidence: 99%
“…The polyamine biosynthetic pathway is a critical regulator of cell growth, differentiation, and cell death, and polyamines are involved in nucleic acid packaging, DNA replication, apoptosis, transcription, and translation 34 . Decreasing activity of odc in specimens of the frog Rhinella arenarum (Hensel) and the plant Hydrocharis dubia (Blume) exposed to organophosphorus pesticides and cadmium has been noted 35 , 36 . Nevertheless, an increase in its activity in the aquatic plants Potamogeton crispus (Linnaeus) and Spirodela polyrhiza (Linnaeus) exposed to lead has been detected 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%